THE MANY-SIDED HUMANISM OF LATVIAN LATGALIAN AND BRASILIAN JESUIT PHILOSOPHER STAŅISLAVS LADUSĀNS - Kiope, Māra (Via Latgalica, 2017)
The famous Latvian born Brasilian philosopher Staņislavs Ladusāns (1913-1993) due to the Soviet occupation could not return to Latvia any more, – as it had been envisaged – to take up a post in the Catholic Faculty of Theology at the University of Latvia. Thus he started his mission in Brazil (1946), where he became a Christian philosopher, known all over the world, especially because of his work “Many-sided gnoseology”, in which he synthesizes phenomenology and Thomism. Specialists in the history of philosophy of Brazil point out that activities initiated by S. Ladusāns brought a profound change in the development of the intellectual culture in Brazil. During the seventies of the 20th century Ladusāns was tackling the philosophical problematics of many-sided humanism. This notion clearly indicates that human understanding is based on a plurality of principles. Thus, in order to describe a human being, one has to illuminate several dimensions, or to perform various types of measurements. Father Ladusāns distinguishes the following dimensions that are of importance for the investigation of the human being: first of all it is gnoseology or the theory of the human capacity for cognition. Above that a human being is to be considered as possessing of immortal soul that determines personal self-esteem. A human being obtains intrinsic value amidst all the other values of economic or technological character. A human being exists in the community; a human being is to be viewed through a vertical dimension revealing the existence of God as the highest being, and through a supra-natural dimension that connects philosophical humanism with the Christian faith, thus providing for spiritual renewal of people. Human beings obtain wishes that go beyond the possibilities offered by the material world; these may be realized only through intensive spiritual life. Such life praxes are accessible only in Christianity; these correspond to the existence of the soul as an immortal spiritual substance encompassed by space and time. The starting point of metaphysics is the thirst of the human being for happiness. The further argumentation of Ladusāns, based on the openness of reason towards Revelation, postulates that God as the Highest Good reveals Himself as love, thus providing our need for inner peace, as it is testified by our inner experience. A person reaches out for infinite Goodness, for the Highest Good, which is the Reality, transcending all other realities. The result of the question of happiness is a practical one – by following the voice of conscience the human being performs choices and acts to deepen the unity with the Highest Good. In doing good things a human being acquires peace. Ladusāns points out that the notion of culture is analogical – that “culture” is equivocally formed and subjectively experienced act of the inner spiritual culture of the person. Equivocal designation means that the inner culture, the spiritual life is attributively used with reference to various manifestations of spirit, forms of artistic expression, etc. – which bear the name of “culture”. By cultivating one’s inner life and the immortal life of the soul, a person reaches such a level of critical competency, which allows to evaluate and to produce new forms of culture. The many-sided spiritual culture provides for personal and national elevation to a much higher level of fullness – reaching the status of love. However, a person is incapable of reaching such a task on his own; one needs cooperation with God. The individual person and a nation has to open up within the spiritual self-identity in the culture of love, so as to reach an increasing pulsation of culture, in order to take a stand against the inhuman ideology – saturated philosophy of modernity and post-modernity.